Supplementary Reading Material for Grade 7 Learners / Ablay, Angela R.... [et al.]. - Ablay, Angela R.; Madredio, Mary May D.S.; Quinan, Nikka D.; Sombrano, Jaecel Lein R.; Miranda, Reina R. (2024)
EXECUTIVE SUMMARY: With the intention of offering supplementary reading material that will help Grade 7 learners to enhance their reading comprehension and as well as teachers to teach reading easier, the researchers conducted a study entitled "Supplementary Reading Material for Grade 7 Learners". The study aimed to determine the evaluation of the developed supplementary reading material for Grade 7 learners at Tanay North National High School during the School Year 2023-2024. This study employed a descriptive-developmental research approach and used an adopted questionnaire-checklist to evaluate the supplementary reading material. The evaluation focused on four aspects: Content, Format, Presentation and Organization, and Accuracy and Up-to-Datedness of Information. To evaluate the supplementary reading material, a total of twelve English teachers participated in the study: five from Bernardo F. San Juan National High School, three from Lagundi-CCL National High School, three from Morong National High School, and one from Tanay North National High School. The developed supplementary material shows that the content is suitable to the student's level of development, provides development of higher cognitive skills such as critical thinking, creativity, learning by doing, inquiry and problem solving, and has the potential to arouse interest of target audience. In conclusion, based on the findings of the study, the developed supplementary reading material in English for Grade 7 Learners may be used in teaching and will help contribute and improve the level of comprehension of the learners. The developed supplementary reading material in English for Grade 7 Learners passed the evaluation of experts in terms of content, format, presentation and organization, and up-to-datedness of information.
Thesis